Correlation of Body Mass Index with Clinicopathologic Parameters in Patients with Idiopathic Membranous Nephropathy [Corrigendum] - Chen X; Chen S; Li Z; Pan X; Jia Y; Hu Z; Niu K; Liu B; Ren Q (Diabetes, Metabolic Syndrome and Obesity)
Chen X, Chen S, Li Z, et al. Diabetes Metab Syndr Obes. 2022;15:1897–1909. The authors have advised the affiliation list on page 1897 is incorrect. The correct author list and affiliations are as follows. Xing Chen,1,2 Shuchun Chen,1,3 Zelin Li,1 Xiaoyu Pan,1 Yujiao Jia,1 Zhijuan Hu,2 Kai Niu,2 Bing Liu,2 Qingjuan Ren1 1Department of Internal Medicine, Hebei Medical University, Shijiazhuang, People’s Republic of China; 2Department of Nephrology, Hebei General Hospital, Shijiazhuang, People’s Republic of China; 3Department of Endocrinology, Hebei General Hospital, Shijiazhuang, People’s Republic of China The authors apologize for this error.